Juridical Review on Collection and Distribution of Royalties for the Use of Copyrights of Song and/or Music on Over-The-Top Services in Indonesia - Silfiani, Diana (Budapest International Research and Critics University, 2022)
Digital Disruption has changed people's way of enjoying entertainment nowadays, and this has been accelerated by the pandemic COVID-19. One of the visible shifts is the way people watch and enjoy entertainment services. Conventional broadcasting institutions such as television, pay-to-play television, and radio, have now found no less powerful competitors: digital platforms and over-the-top services. In Indonesia, the market share of television and subscription television services will be severely shaken by the discontinuation of 18 cable/pay television networks belonging to the Disney group and will focus on streaming services or its over-the-top service, namely Disney+. Various similar services such as Netflix, VIU, GoPlay, WeTV and others also compete for market share in OTT services. OTT is relatively new in Indonesia, so the regulations governing it are still not comprehensive and detail. The content displayed by OTT contains numerous copyrights and neighbouring rights of the song works, those of belonging to the Songwriter, Performer and the Phonogram Producer. Copyrights in Indonesia is regulated in Law no. 28 of 2014 on Copyrights, and the Law does not yet regulate the use of copyrights and neighbouring rights in OTT services. Law No. 32 year 2002 on Broadcasting has not accommodated over-the-top services as broadcasting institutions. The Decision of Indonesian Constitutional Court No. 39/PUU-XVIII/2020 stipulates that OTT content cannot be equated with linear television content, the Constitutional Court rejected the proposal to change the definition of a broadcasting institution to include OTT as a broadcasting institution. This of course will affect the collection of song copyright’s royalties in Indonesia, given Government Regulation no. 56 of 2021 on Management of Royalties of Song and/or Music does not specifically regulate OTT, only regulates broadcasting institutions. These absences certainly does not reduce the obligation of the OTT to fulfil its obligations to the Songwriter and/or Copyrights’ holder by the reason it is not regulated in details by laws and regulations. A regulation that stipulates the existence, use and matters related to copyrights in OTT is very necessary. This topic will be analyzed qualitatively and combined with facts in Indonesia and worldwide regarding implementation of collection and distribution of royalties of copyright of the song and/or music in Indonesia. This paper intends to further examine the obligation to pay royalties of the song and/or music copyrights by over-the-top services in Indonesia.